Solve the inequality 4t^2 \le -9t + 12 - 4t + 23 + (2t - 1)(2t + 1). Write your answer in interval notation.

learnmgcat Aug 10, 2024

#1**+1 **

First, let's simplify the right hand side of the equation a little bit.

We get that \(-9t+12-4t+23+4t^2-1=-13t+4t^2+34\)

Now, we simply move all terms to one side. Note that most terms cancel out.

we get the equation

\(13t-34\le \:0\)

Solving for t, we get

\(13t\le \:34\\t\le \:\frac{34}{13}\)

In interval notation, this is

\((-inf, \frac{34}{13}]\)

Thanks! :)

NotThatSmart Aug 10, 2024